The significance of the crosstalk between ubiquitination or deubiquitination and ncRNAs in non-small cell lung cancer - Sun, Yiyang; He, Ping; Li, Li; Ding, Xue (Frontiers in Oncology, 2023)
Lung cancer (LC) remains the leading cause of cancer-related deaths worldwide, with extremely high morbidity and mortality rates. Non-small cell lung cancer (NSCLC) is the most critical type of LC. It seriously threatens the life and health of patients because of its early metastasis, late clinical symptoms, limited early screening methods, and poor treatment outcomes. Non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), participate in cell proliferation, metastasis, and chemoresistance. Several previous studies have proven that ncRNAs are vital regulators of tumorigenesis. Ubiquitination plays the most crucial role in protein post-translational modification (PTM). The reversible ubiquitination process is called deubiquitination. In summary, ubiquitination and deubiquitination play essential roles in mediating the degradation or overexpression of a range of crucial proteins in various cancers. A growing number of researchers have found that interactions between ncRNAs and ubiquitination (or deubiquitination) play a crucial role in NSCLC. This review presents several typical examples of the important effects of ncRNAs and ubiquitination (or deubiquitination) in NSCLC, aiming to provide more creative ideas for exploring the diagnosis and treatment of NSCLC.